The trench - Alten, Steve (Kensington Pub., 2018)
A giant shark escapes from a California aquarium, creating havoc before heading to sea. As he probes the ocean depths in pursuit, biologist Jonas Taylor stumbles on a terrorist nuclear arms factory.